The impact of lighting in halls, amphitheaters, and halls on the security and nighttime attractiveness of concert spaces and the application of smart technology (Case study: Sohrab Pakzad's Spinace Hotel Concert) - Gohari, Sepideh (International journal of Modern Achievement in Science, Engineering and Technology, 2026)
I present a brief and practical summary of intelligent lighting for halls, amphitheaters and concert halls. The aim of this summary is to provide an overview, with key points and implementation elements, so that you can easily use it for a project proposal or team meeting. Smart Lighting for Large Performance Spaces: Harmonizing Light, Sound, and Image with Automation and Machine Learning for an Audience-Centered Experience Key Objectives: Create a coherent visual experience aligned with the music and the stage narrative Reduce setup time and human errors with automation and data-driven Improve energy efficiency and sustainability with intelligent management of lighting consumption Provide secure access and control for the technical team and lighting manager Architectural Elements of Smart Lighting Central Light Control Combination of surface lighting (wash), spot lighting, and moving heads DMX/Art-Net/sACN control platform with routing and assignment of concerns to stage objects Time and musical inputs BPM, music structure (Intro/Verse/Chorus/Drop), dynamic oscillation Stage events such as artist entrance/exit, fireworks, video logs Artificial intelligence and data-driven music analysis to extract BPM, phases, and energy of light cues Intelligent suggestion of cues based on the style of performances and the experience of the coordination team With Video Walls and LED Wall for color and rhythm coordination Automation and dynamic display Cue editor with Live Tweaks and recording of modified versions of the light driver based on phases and sound intensity with simultaneous predictions Technical team user experience User-friendly UI/UX for the lighting manager and technician with equipment status dashboard Scene simulator for testing Cues without the need for live execution Security and sustainability Access management, change logs, project versioning Fast backup and recovery in case of power outages or network errors Optimization of consumption and sustainability Energy consumption assessment of each Cue and recommendation of low-power alternatives Equipment thermal monitoring and maintenance prediction Operation security and emergency control Safe shutdown methods, fast recovery, and implementation of safe maps for emergency scenarios Proposed implementation approach (brief)Requirements and basic architecture review Analysis of space, existing equipment, budget, constraints Mechanical Define Cue Naming Standard and Initial Metadata Basic Implementation Connect Light to DAW/Mixer with MIDI/OSC Set up DMX/Art-Net/sACN protocols and cue manager Simulation and Testing Create a simulation environment to test Cues before execution Test the coordination of light with music and video Trial run and feedback Limited run with light and video technology team Gather feedback and corrections Continuous deployment and optimization Update AI models, hardware maintenance and documentation Key points for successful implementation Standardization: Cue Naming and Metadata comprehensively from the beginning of the project Integrate with the show production process: from pre-production to live execution Security and stability: Access, backups, and detailed logging User experience: Simple UI and simulation capabilities for technical and directing teams Measurement and improvement: Dashboard reporting on energy consumption, delays, and quality VisualExample of actionable elements Provide a checklist for making decisions about equipment (DMX/Art-Net, LED walls, moving heads) Prepare a standard cue template with naming and suggested metadata Design a modular architecture of the lighting system and communication protocols with a target budget Visual effects of light on video graphics, Lighting design appropriate to different spaces of the hall, Lighting architecture and stage lighting o BPM, music structure (Intro/Verse/Chorus/Drop), dynamic oscillation o Stage events such as artist entrance/exit, fireworks, videologs o AI and data-driven o Music analysis to extract BPM, phases, and energy Light Cues Intelligent suggestion of Cues based on performance style and experience Team coordination with Video Walls and LED Wall for color and rhythm coordination Automation and dynamic display Cue editor with Live Tweaks and recording modified versions of the light driver based on phases and sound intensity with simultaneous predictions Technical team user experience o User-friendly UI/UX for the lighting manager and technician with equipment status dashboard o Scene simulator for testing Cues without the need for live execution Security and sustainability o Access management, change logs, project versioning o Fast backup and recovery in case of power outages or network errors Consumption optimization and sustainability o Energy consumption assessment of each Cue and suggestion of low-power alternatives o Thermal monitoring of equipment and maintenance prediction Emergency operation and control security o Safe shutdown methods, fast recovery, and implementation of safe maps for emergency scenarios Proposed implementation approach (brief) Review of needs and basic architectureo Analysis of space, existing equipment, budget, constraints Mechanical Define Cue naming standard and initial metadata Basic implementation Connect lighting to DAW/Mixer with MIDI/OSC Set up DMX/Art-Net/sACN protocols and cue manager Simulation and testing Create a simulation environment to test cues before executiono Test lighting coordination with music and video Trial run and feedback Limited run with lighting and video technology team Collect feedback and corrections . Continuous deployment and optimization Update AI models, maintain hardware, and document Key points for successful implementation Standardization: Cue naming and metadata comprehensively from the beginning of the project Integration with the show production process: from pre-production to live execution Security and stability: Access, backups, and accurate logging User experience: Simple UI and simulation capabilities for technical and directing teams Measurement and improvement: Dashboard reporting on energy consumption, delays, and visual quality Example of actionable elements for the next meeting Provide a checklist for making decisions about equipment (DMX/Art-Net, LED walls, moving heads) Prepare a standard cue template with naming and suggested metadata Design a modular architecture of the lighting system and communication protocols with a target budget Define KPIs to evaluate the success of the project If you like, I can: Create a step-by-step implementation checklist for your project Design a standard cue template with naming and precise metadata Prepare a technical architecture map with suggested protocols, tools, and instruments for your budget Please tell me: D Size of the venues and type of concerts (live or recorded) Your current or desired equipment (DMX/Art-Net, moving heads, LED walls) n Do you prefer the lighting to be fully intelligently synchronized with the music or is just automation and cue timing sufficient Is it?